YOUTH POLITICAL PARTICIPATION IN THE ERA OF MEMES AND HASHTAG ACTIVISM: A MEDIA AND COMMUNICATION ANALYSIS - Suardi, Suardi (Cognitionis Civitatis et Politicae, 2025)
The rise of digital platforms has radically transformed the landscape of political participation, particularly among youth, with memes and hashtag activism emerging as prominent tools for engagement. This research investigates the role of these digital tools in shaping youth political behavior, examining how memes and hashtags influence political discourse, mobilization, and activism. The study aims to explore how young people engage with political issues through these platforms and whether this participation leads to meaningful real-world action. A mixed-methods approach was employed, combining content analysis of viral political memes and hashtag campaigns, with surveys and interviews of youth participants engaged in digital activism. The findings indicate that while youth engagement with political memes and hashtags is widespread, it tends to remain symbolic and does not always translate into traditional forms of political participation, such as voting or attending protests. Political memes were found to foster awareness and spark discussions, but their impact on tangible political change was limited. The study concludes that while memes and hashtags play an important role in raising awareness, they often represent a form of digital activism that lacks long-term engagement and actionable outcomes. To bridge this gap, future efforts should focus on integrating digital tools with offline political engagement.